Infectious diseases consultations at a South African academic hospital: a six-month review of inpatient consultations - Richards, Lauren Carol (My University, 2019)
ABSTRACT Background The infectious diseases (ID) department is becoming increasingly valuable in an era of evolving antimicrobial resistance and an enlarging immunocompromised population. To date, there has been little evaluation of the infectious diseases consultation services in South African hospitals. Methods A review of ID inpatient consultations was performed over a period of six months at Helen Joseph Hospital, a South African tertiary hospital. Data from each consultation was recorded on a computerised database and analysed. Results A total of 749 ID consultations were reviewed representing an average of 4.8% of hospital admissions. The most common reasons for consultation were for initiation of antiretroviral therapy (ART) (27.8%), lipoarabinomannan antigen (LAM) testing (24.8%) and change of ART (21.6%). Of all patients reviewed, 93.3% were human immunodeficiency virus (HIV) positive and the median CD4 count was 52 cell/mm3. The infectious diagnoses (excluding HIV) that were most frequently encountered were pulmonary and abdominal tuberculosis (TB) and acute gastroenteritis. When all subcategories of TB infection were combined, 42.9% of patients reviewed were found to be infected with TB. The most common non-infectious co-morbidities were acute kidney injury, hypertension and diabetes mellitus. Conclusion The ID department sees a high volume of cases. HIV, TB and their management dominate the workload and the patient disease profile. Non-infectious comorbidities were infrequent in this population, possibly due to the relatively young median age. Due to the large numbers of HIV- and TB-related cases, only a small proportion of the inpatient ID service was devoted to antibiotic stewardship, infection prevention and control, and the spectrum of cases seen more frequently by ID departments in the developed world.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment for the requirements of the degree of Master of Medicine in Internal medicine Johannesburg 2019